On Translations of the Emerald to Ruthenian - Чистякова, Марина (Poznańskie Studia Slawistyczne, 2018)
Several attempts were made in the Kyiv Metropolis to translate the basic version of the Emerald (Izmaragd) from Church Slavonic to Ruthenian. These translations were fragmentary, though. The oldest translation, limited to 17 initial chapters of the Emerald, is known in the version dating back to the last quarter of the 15th century. This translation was later partially (8 сhapters) used in compiling the Gnojno version of the Emerald, which consisted of 29 texts in Ruthenian. At least four other Ruthenian chapters from the Emerald dating back to late 16th century are contained in the collection from Pavel Simson’s compendium No 2. Another three texts are found in a collection which dates back to early 17th century and is stored in the Andrey Sheptytsky National Museum in Lviv.